Coinfection of Chlamydia psittaci and Enterococcus faecalis exacerbated respiratory distress in patients: from isolation to mouse model - Zhang, Xuedi; Wang, Yihui; Wang, Yuhan; Cui, Yuehui; Wang, Huimin; Huang, Zongyang; Luo, Lin; Tang, Linlin; Chen, Jianlin; He, Cheng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study aimed to isolate and identify Chlamydia psittaci (C. psittaci) and Enterococcus faecalis (E. faecalis) from a patient suspected of community-acquired pneumonia.MethodsThe samples from the patient (lung lavage and throat swab) and his son (throat swab) were tested to determine antibodies against COVID-19 and C. psittaci-specific IgG. Afterward, 40 female mice were inoculated intranasally with coinfection of C. psittaci and E. faecalis and primary infection of C. psittaci followed by E. faecalis. Meanwhile, eight mice with C. psittaci and E. faecalis infection alone served as the control group. Clinical signs, lung lesions, and pathogen loads were monitored.ResultsPositive C. psittaci genomics were detected in both the patient’s lung lavage and his son’s swabs, while C. psittaci and E. faecalis were isolated and identified from the patient’s lung lavage samples. Moreover, positive C. psittaci-specific IgG and negative COVID-19 antibodies were determined. The patient recovered after 10-day doxycycline treatment. Mice showed weight loss, breathing difficulties, and diffuse alveolar damage after inoculation with C. psittaci followed by E. faecalis.ConclusionOur experiment demonstrated that coinfection, particularly sequential infection with C. psittaci followed by E. faecalis, can duplicate severe respiratory distress and typical pathological lesions.